A holistic approach to the introduction of automatic speech recognition technology in ground combat vehicles. - Leggatt AP; Noyes JM (Military Psychology, 2004)
Recent advances in speech recognition technology prompt consideration of using machine recognition of human speech in a wider range of applications. Communication using speech recognition has a number of benefits. One area where this technology has only recently been considered is in military armored lighting vehicles during combat. A holistic approach to considering speech recognition in this form of transport is reported here by viewing this technology within the context of the cockpit re- source management paradigm. This facilitated development of a function-based crew communication model. It is within this framework that the use of speech recognition in armored vehicles is evaluated. The use of speech technology led to a reduction in the total amount of communication taking place in the vehicle.